The burden of chronic diseases across Europe: what policies and programs to address diabetes? A SWOT analysis - Angela Giusti; Marina Maggini; Sofia Colaceci (BMC, 2020)
Abstract Background Promoting the well-being at all ages and reducing premature mortality from non-communicable diseases (NCDs) is a major target of the Sustainable Development Goals. In the frame of the JA-CHRODIS, a Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis was conducted to provide different countries' insights on what makes a policy/programme addressing NCDs applicable, sustainable and effective, with a focus on diabetes. Methods A qualitative study has been performed using a SWOT analysis on policies/programmes at the national/federal or subnational level. Results By March 2016, 14 SWOTs were conducted involving 11 European countries and 57 stakeholders and Ministries of Health, reporting and analysing a total of 44 policies. The main strengths, weaknesses, opportunities and threats have been outlined as well as and the main areas for governance improvement. A binding trans-sectoral approach is necessary to tackle the underlying risk factors of inequalities. The culture of disease prevention and health promotion is still low while the biomedical paradigm prevails. A systematic gender perspective is still missing. Sharing and exchange of best practices, as sponsored by the European Commission, is acting as a motivator. Conclusion The SWOT analyses draw an overall picture of the complexity of designing and implementing good policies and programmes that are tailored to local needs. These results may apply to any context and can be used by decision-makers, managers, professionals and other stakeholders to focus on key issues, recognising areas for attention.